Threshold exposure duration for recognition of test objects in children with various refractive statuses (Ukrainian Journal of Ophthalmology, 2026)
Backup: The speed of visual information processing is of primary importance today.Purpose: To determine the threshold exposure duration for recognition of test objects (TEDRTO) values in children with various refractive statuses.Materials and Methods: Seventy one children (22 hyperopes, 26 myopes, and 23 emmetropes; 142 eyes totally) aged 7 to 13 years underwent TEDRTO measurements with the electronic apparatus. A child fixated on a test object (TO) subtending 160, 40 or 8 minutes of arc (ma).Results: The monocular TEDRTO values in emmetropes, hyperopes and myopes were 1.0 ms with a TO subtending 160 ma; 1.4±0.2 ms, 1.8±0.2 ms and 1.8±0.2 ms, respectively, with a TO subtending 40 ma; and 7.8±1.1 ms, 14.9±1.3 ms, and 7.9±1.0 ms, respectively, with a TO subtending 8 ma. Binocular TEDRTO values tended to be lower than monocular ones for optotypes subtending 40 and 8 ma.Conclusion: TEDRTO values were found to increase significantly as the visual angle subtended by the TO decreased, which could be explained by a longer time required for recognition of a high-frequency image compared to that of a low-frequency image. Significantly higher TEDRTO values in hyperopes compared to emmetropes and myopes (P
Keywords: threshold exposure duration for recognition of test objects; refractive anomalies; emmetropia; hyperopia; myopia